Intermunicipal inequities in access and use of secondary health services in the metropolitan area of Curitiba - Sandra Lúcia Vieira Ulinski Aguilera; Beatriz Helena Sottile França; Simone Tetu Moysés; Samuel Jorge Moysés (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
The aim of this study was to identify and analyze inequities in the access to specialized services in the municipalities of the metropolitan area of Curitiba, Paraná, Brazil. This is an ecological study. In its preparatory stage, this study focused on the socioeconomic, epidemiologic, healthcare network and sectoral financing network profiles of the 26 municipalities comprising this area. Factor analysis was employed to obtain the six principal components, and a synthetic index was calculated from them, allowing municipalities to be ranked according to living conditions and health situation. Primary data was collected from 24 municipalities, regarding their capacity, directed and repressed demand of specialized healthcare services. The context analysis revealed accentuated intermunicipal inequities. The synthetic index allowed municipalities to be classified in four relatively homogeneous groups regarding living and health conditions. Municipalities located in Vale do Ribeira obtained the worse outcomes for the Living Conditions and Health Situation Synthetic Index, as well as the higher repressed demand for specialized healthcare services. The geographical distance from the capital showed to contribute to worse living and health conditions and greater difficulties in access to healthcare services.